Design and Implementation of 2x4 Octagonal Array Patch Microstrip Antennas using T-Slots at 2.4 GHz Frequency for Wifi Applications - Muhammad Ibnu Muttaqin; Hendro Darmono; Koesmarijanto Koesmarijanto (Jurnal Jaringan Telekomunikasi, 2023)
Wireless communication requires a useful device to transmit and receive electromagnetic waves. WiFi is a particular kind of wireless communication device used to send data over the internet network. The bandwidth and signal coverage of WiFi have significant limitations. As a result, an antenna is utilized to enhance signal reception in order to solve this issue. The research method used is to compare the design of the 2x4 octagonal microstrip array antenna using a T-slot and without the T-slot to see the results of simulation and testing in terms of return loss, VSWR, gain, and bandwidth. The results of bandwidth testing for octagonal microstrip antennas without a 2x4 T-slot array are 32 MHz, while for octagonal microstrip antennas using a 2x4 T-slot array of 40MHz. The octagonal microstrip antenna without a 2x4 T-Slot array has Return Loss of -18.2 dB and a VSWR of 1.280. The 2x4 octagonal T-Slot array microstrip antenna has Return Loss of -17.6 dB and a VSWR of 1.303. The test results 2x4 octagonal array microstrip antenna gain without using T-slot produces the largest gain of 9.55dBi, and the antenna using T-slot produces the largest gain of 12.55dBi.